2007
DOI: 10.1002/esp.1611
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the Relationship Between Typhoon‐Triggered Landslides and Critical Rainfall Conditions

Abstract: Many landslides are triggered by rainfall. Previous studies of the relationship between landslides and rainfall have concentrated on deriving minimum rainfall thresholds that are likely to trigger landslides. Though useful, these minimum thresholds derived from a log-log plot do not offer any measure of confidence in a landslide monitoring or warning system. This study presents a new and innovative method for incorporating rainfall into landslide modelling and prediction. The method involves three steps: compi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 44 publications
1
69
0
Order By: Relevance
“…Despite numerous slope stability models have been developed (e.g. Montgomery and Dietrich 1994;Iverson 2000;Borga et al 2002;Liao et al 2011;Formetta et al 2014;Ho and Lee 2016;Thiery et al 2017), the fundamental controls leading to slope failure driven by rainfall are still not well quantified (Borja et al 2012), and thus the improvement of current models is still an important research topic (Chang et al 2008). The difficulty of building up reliable mathematical models lies in the numerous variables involved in the triggering process, such as spatial and temporal rainfall variability, mechanical and hydraulic soil properties, slope morphology, vegetation coverage, initial soil suction and moisture (Greco et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Despite numerous slope stability models have been developed (e.g. Montgomery and Dietrich 1994;Iverson 2000;Borga et al 2002;Liao et al 2011;Formetta et al 2014;Ho and Lee 2016;Thiery et al 2017), the fundamental controls leading to slope failure driven by rainfall are still not well quantified (Borja et al 2012), and thus the improvement of current models is still an important research topic (Chang et al 2008). The difficulty of building up reliable mathematical models lies in the numerous variables involved in the triggering process, such as spatial and temporal rainfall variability, mechanical and hydraulic soil properties, slope morphology, vegetation coverage, initial soil suction and moisture (Greco et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Visual interpretation of post-event orthophotos revealed that Typhoon Aere caused 703 landslides in the Shihmen Reservoir watershed (Chang et al 2008), whereof 421 landslides occurred in the Baichi catchment Chiang and Chang 2009). Most of the observed slope failures in the Baichi catchment are shallow landslides that occur on slopes with a soil depth less than 2 m ).…”
Section: Typhoon-induced Landslides and Debris Flows In The Baichi Camentioning
confidence: 99%
“…Weather radar has significant advantage over rain gauge since it can obtain the spatial-temporal variations of the precipitation field (Chang et al 2008;Chen et al 2007;Morrissey et al 2004;Yu and Cheng 2008). In order to understand the major storm contribution to the precipitation distribution over the Dongjiang reservoir basin, our investigations tried to examine the radar reflectivity data of 1200-1800 UTC on July 14, 2006, at 1-km 2 spatial resolution and about 6-min temporal resolution to analyze the evolution of the major storm (Figs.…”
Section: Temporal Evolution Of Radar Reflectivitymentioning
confidence: 99%